Density and refractive index measurements of transition-temperature mixture (deep eutectic analogues) based on potassium carbonate with dual hydrogen bond donors for CO2 capture - Ghaedi, H. (Academic Press, 2018)
The transition-temperature mixture (TTM) is a new type of solvent and is known as a tuneable solvent similar to deep eutectic solvent (DES). The new type of solvent called ternary transition-temperature mixture (TTTM) was prepared to use for CO2 capture purposes. In this work, TTMs and TTTMs were prepared with potassium carbonate (PC) as a hydrogen bond acceptor (HBA) and three hydrogen bond donors (HBDs) such as glycerol (GL), ethylene glycol (EG) and 2-amino-2-methyl-1-3-propanediol (AMPD) known as a hindered amine (HA). Binary TTMs were PC-GL with mole ratios 1:10 and 1:16 and PC-EG with the same mole ratios. TTTMs were prepared by adding AMPD in binary TTMs such as PC-GL-AMPD 1:16:1 and PC-EG-AMPD 1:10:1. The experimental density and refractive index of all mixtures were measured at temperatures from 293.15 K to 343.15 K with an interval of 5 K. The effect of temperature, mole ratio, molar massand alkyl chain length on the properties was investigated. The molar volumes and isobaric thermal expansion were calculated using experimental density data. The experimental refractive index values were used to derive the specific refraction, molar refraction, free molar volume, electronic polarization and polarizability at several temperatures. Â© 2017 Elsevier Ltd